GLOBAL PERSPECTIVE OF CONSUMER BEHAVIOUR DURING COVID-19 - Shamsher, Robaka (International Journal of Marketing Research Innovation, 2022)
The coronavirus (COVID-19) pandemic has triggered the most significant global repercussions. This global crisis has drastically transformed consumers' market needs, attitudes,s and purchase intentions. The new market dynamics have taught consumers to set new priorities regarding their shopping habits and consumer behavior. This study examines the global perspective of changing consumer behavior during COVID-19 and reveals the sustainability of which behavioral changes are permanent. This study is based on descriptive research as it describes the changes in consumer behavior during the COVID-19 pandemic. The research design has been conducted using by secondary data method to analyze the changing behavioral perceptions. The results of the study revealed four aspects of behavioral changes. These are changes in shopping behavior, changes in spending behavior, changes in consumer behavior, and changes in brand loyalty. The study's findings also divulged that some consumer behavioral transformations could be endured after the pandemic. This study has important implications for professionals and academicians in adopting marketing decisions by integrating the fluctuating demands of consumers through communicating suitable marketing strategies to survive the transference of consumer behavior instigated by the pandemic.JEL Classification Codes: D10, M31.